PDlim2 selectively interacts with the PDZ binding motif of highly pathogenic avian H5N1 influenza A virus NS1. - Jia Yu (Public Library of Science (PLoS), 2011)
The multi-functional NS1 protein of influenza A virus is a viral virulence determining factor. The last four residues at the C-terminus of NS1 constitute a type I PDZ domain binding motif (PBM). Avian influenza viruses currently in circulation carry an NS1 PBM with consensus sequence ESEV, whereas human influenza viruses bear an NS1 PBM with consensus sequence RSKV or RSEV. The PBM sequence of the influenza A virus NS1 is reported to contribute to high viral pathogenicity in animal studies. Here, we report the identification of PDlim2 as a novel binding target of the highly pathogenic avian influenza virus H5N1 strain with an NS1 PBM of ESEV (A/Chicken/Henan/12/2004/H5N1, HN12-NS1) by yeast two-hybrid screening. The interaction was confirmed by in vitro GST pull-down assays, as well as by in vivo mammalian two-hybrid assays and bimolecular fluorescence complementation assays. The binding was also confirmed to be mediated by the interaction of the PDlim2 PDZ domain with the NS1 PBM motif. Interestingly, our assays showed that PDlim2 bound specifically with HN12-NS1, but exhibited no binding to NS1 from a human influenza H1N1 virus bearing an RSEV PBM (A/Puerto Rico/8/34/H1N1, PR8-NS1). A crystal structure of the PDlim2 PDZ domain fused with the C-terminal hexapeptide from HN12-NS1, together with GST pull-down assays on PDlim2 mutants, reveals that residues Arg16 and Lys31 of PDlim2 are critical for the binding between PDlim2 and HN12-NS1. The identification of a selective binding target of HN12-NS1 (ESEV), but not PR8-NS1 (RSEV), enables us to propose a structural mechanism for the interaction between NS1 PBM and PDlim2 or other PDZ-containing proteins.